Effects of agricultural land use on sediment and nutrient retention in valley-bottom wetlands of Migina catchment, southern Rwanda. (1st August 2018) - Uwimana, Abias; van Dam, Anne A.; Gettel, Gretchen M.; Irvine, Kenneth
Abstract: Factors affecting the retention and export of water, sediments (TSS), nitrogen (TN) and phosphorus (TP) were examined in the Migina river catchment, southern Rwanda from May 2012 to May 2013. Landscape characteristics and seasonal changes in land use and land cover (LULC), rainfall, discharge, and area-specific net stream yields of TSS, TP and TN were measured monthly in 16 reaches of the Munyazi sub-catchment with five valley bottom LULC categories (grass/forest, ponds/reservoirs, ploughed, rice, and vegetables). Valley bottoms dominated by grass/forest and ponds/reservoir types were generally associated with positive net yields of nutrients and sediments, while those with agricultural land covers had a net negative yields, resulting in net export. Water was retained only in reaches with ponds/reservoirs. Seasonally, there was a strong relationship between net yield and discharge, with 93%, 60% and 67% of the annual TSS, TP and TN yields, respectively, transported during 115 days with rain. During low flow periods, all LULC types had positive net yields of TSS, TP and TN (suggesting retention), but during high flow periods had negative net yields (suggesting export). Significant effects of hillside land use on sediment and nutrient yields were also found. Stream and river water quality in Rwandan valley bottoms are at risk of further deterioration due to declining natural ecosystems (grassland and forest) and increasing agricultural and urban development. It is important to adopt appropriate land management practices (minimal tillage, optimization of water use, strategic implementation of retention ponds and vegetation buffer zones) to intercept TSS, TP and TN in runoff from storm water and agricultural areas. Special attention is needed for critical periods of the year when farming activities (e.g. land preparation, fertilizer application) coincide with high flow events. Highlights: Sixteen river reaches in valley bottoms in southern Rwanda were identified and classified into five land use categories. Sediment and nutrient yields were positive in reaches with natural vegetation or reservoirs, negative with agriculture. Reaches were more vulnerable to export of sediment and nutrients with peak flows when used for agriculture. As high flow periods coincide with agricultural activities, improved practices can reduce sediment and nutrient export.